2020
DOI: 10.1038/s41598-020-74703-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram predicting the risk of positive biopsy for patients in the diagnostic gray area of prostate cancer

Abstract: The roles played by several inflammatory factors in screening for prostate cancer (PCa) among gray area patients, namely those with serum prostate-specific antigen (PSA) levels between 4 and 10 ng/ml, have not been completely identified, and few effective diagnostic nomograms have been developed exclusively for these patients. We aimed to investigate new independent predictors of positive biopsy (PB) results and develop a novel diagnostic nomogram for this group of patients. The independent predictors of PB re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Also, a recent in vitro study showed that the monocyte cell lines promoted the progression of prostate cancer cells through increased activity of monocyte chemotactic protein‐1 expression and nuclear factor kappa B activity 25 . In accordance with this accumulating evidence, the three recent studies reported that the lymphocyte‐to‐monocyte ratio was a significant factor that influenced the overall detection rate of prostate cancer 21–23 . However, the recent study by Li et al 11 reported that the lymphocyte‐to‐monocyte ratio was not associated with the overall detection rate of prostate cancer.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Also, a recent in vitro study showed that the monocyte cell lines promoted the progression of prostate cancer cells through increased activity of monocyte chemotactic protein‐1 expression and nuclear factor kappa B activity 25 . In accordance with this accumulating evidence, the three recent studies reported that the lymphocyte‐to‐monocyte ratio was a significant factor that influenced the overall detection rate of prostate cancer 21–23 . However, the recent study by Li et al 11 reported that the lymphocyte‐to‐monocyte ratio was not associated with the overall detection rate of prostate cancer.…”
Section: Discussionmentioning
confidence: 77%
“…Also, to date, only a few studies involving small‐ or medium‐sized cohorts have tested the predictive role of lymphocyte‐to‐monocyte ratio in detecting prostate cancers. The studies have reported conflicting results 11,21–23 . Furthermore, there exist minimal data on the use of lymphocyte‐to‐monocyte ratio or eosinophil‐to‐lymphocyte as a significant factor influencing the detection of clinically significant cancers.…”
Section: Discussionmentioning
confidence: 99%
“…( 42 ) reported that PCa patients with higher pre-treatment and post-treatment RDW levels had poorer 3-year overall survival and cancer-specific survival. One study reported that RDW could be used to develop a novel nomogram to predict the risk of positive biopsy for patients with gray area of PSA ( 43 ). In addition, Fukuokaya W, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive forms of PCa are mainly associated with lower fPSA percentage values. 11 fPSA is comprised of different molecular forms: alongside the intact form of PSA (iPSA) we find the precursor form proPSA, which is associated with cancer, and benign PSA (bPSA), associated primarily with BPH. 12 Different truncated forms of proPSA can be detected in the serum alongside the native form [−7]proPSA.…”
Section: Introductionmentioning
confidence: 92%